Photodynamic Therapy in Dermatology - Gold, Michael H.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Photodynamic Therapy in Dermatology is the first book to cover global research on photodynamic therapy (PDT) in the management of skin disease. Although a relatively young procedure, PDT has enjoyed increased popularity during the last ten years. As research has grown, two distinct routes have appeared: the United States model and the European one, each focusing on different uses and photosensitizers. Dr. Gold has assembled the world$1 (Bs experts on PDT to create a book that concisely covers every use and photosensitizer available around the world and includes comprehensive coverage of both of the FDA-approved photosensitizers in the United States, all the while carefully differentiating between off-label and FDA-approved uses of photodynamic therapy. Photodynamic Therapy in Dermatology emphasizes how to integrate PDT into practice. Toward this end, it is organized by disease category, with each chapter providing a systematic discussion of indications, PDT approaches from country to country, common side effects, prognosis as well as the underlying science. The book will be of value to dermatologists seeking a state-of-the-art review of PDT around the world, the latest in its clinical uses, and guidance on how to incorporate PDT into clinical practice.s
Keywords: Medicine; Dermatology; Medicine & Public Health; Dermatology